Emergency treatment of peri‐operative anaphylaxis: Resuscitation Council UK algorithm for anaesthetists - Dodd, A.; Turner, P. J.; Soar, J.; Savic, L. (Anaesthesia, 2024)
Peri‐operative anaphylaxis is a rare but potentially catastrophic event which must be considered whenever unexpected and significant cardiovascular or respiratory compromise occurs during anaesthesia. The Resuscitation Council UK algorithm for peri‐operative anaphylaxis highlights the importance of early intravenous adrenaline and fluid resuscitation and provides guidance on the treatment of refractory anaphylaxis and immediate follow‐up. This algorithm is endorsed by the Royal College of Anaesthetists, Association of Anaesthetists, British Society of Allergy and Clinical Immunology and Clinical Immunology Professional Network of the British Society for Immunology. This document was produced by the Perioperative Allergy Network steering committee in collaboration with the Resuscitation Council UK.